Dose–time fractionation schedules of preoperative radiotherapy and timing to surgery for rectal cancer. (February 2020) - Jin, Fu; Luo, Huanli; Zhou, Juan; Wu, Yongzhong; Sun, Hao; Liu, Hongliang; Zheng, Xiaodong; Wang, Ying
Chemoradiotherapy (CRT) is extensively used prior to surgery for rectal cancer to provide significantly better local control, but the radiotherapy (RT), as the other component of CRT, has been subject to less interest than the drug component in recent years. With considerable developments in RT, the use of advanced techniques, such as intensity-modulated radiotherapy (IMRT) in rectal cancer, is garnering more attention nowadays. The radiation dose can be better conformed to the target volumes with possibilities for synchronous integrated boost without increased complications in normal tissue. Hopefully, both local recurrence and toxicities can be further reduced. Although those seem to be of interest, many issues remain unresolved. There is no international consensus regarding the radiation schedule for preoperative RT for rectal cancer. Moreover, an enormous disparity exists regarding the RT delivery. With the advent of IMRT, variations will likely increase. Moreover, time to surgery is also quite variable, as it depends upon the indication for RT/CRT in the clinical practices. In this review, we discuss the options and problems related to both the dose–time fractionation schedule and time to surgery; furthermore, it addresses the research questions that need answering in the future.